Immobilization of Lipase on Surfactant-Modified Bentonite and Its Application for Biodiesel Production from Simulated Waste Cooking Oil - Ruth Chrisnasari; Angelina Yonardi; Hesti Lie; Restu Kartiko Widi; Maria Goretti Marianti Purwanto (UNEJ e-Proceeding, 2014)
The influence of bentonite modification by cationic surfactant hexadecyl-trimethyl-ammonium bromide (HDTMA-Br) and tetramethyl ammonium hydroxide (TMAOH) on its capability to immobilize lipase was studied. Modification of bentonite was conducted by the adding of 4-6% (v/v) HDTMA-Br and TMAOH respectively. The obtained immobilized lipases then were characterized to observe the optimum pH and temperature as well as their stability during reuse application. The observed results show that there is no significant difference between the variations of HDTMA-Br concentrations to the percentage of immobilized enzyme which can immobilize lipase up to 75-78%. However, the best concentration of TMAOH is 4% (v/v) which can immobilize lipase up to 97.95%. The obtained immobilized lipases on HDTMA-Br-modified bentonite show the optimum catalytic activity on reaction temperature of 35-40 oC and pH of 7.5. In other hand, the optimum catalytic activity of immobilized lipases on TMAOH-modified bentonite is 40oC of incubation temperature and pH of 7. The immobilized lipases on both HDTMA-Br and TMAOH modified bentonite are stable enough so it could be re-used four times before its activity decreased by 48,565% and 46.83 % respectively. Keywords: Lipase, Cationic Surfactant, Bentonite, HDTMA-Br, TMAOH, Biodiesel, Immobilization.